A Combination of Boolean Games with Description Logics for Automated Multi−Attribute Negotiation - Lukasiewicz, T; Ragone, A (CEUR−WS.org, 2009)
Multi-attribute negotiation has been extensively studied from a game-theoretic viewpoint. In negotiation settings, utility functions are used to express agent preferences. Normal and extensive form games, however, have the drawback of requiring an explicit representation of utility functions, listing the utility values for all combinations of strategies. Therefore, several logical preference languages have been proposed, to specify multi-attribute utility functions in a compact way. Among these approaches, there are also Boolean games. In this paper, we introduce Boolean description logic games, which are a combination of Boolean games with ontological background knowledge, formulated using expressive description logics. In this way, it is possible to enhance the expressiveness of preference representation, maintaining the advantages of the game-theoretic approach. We include and discuss several generalizations, showing their practical usefulness within a service negotiation scenario. Furthermore, we also provide complexity results.